2022
DOI: 10.1002/hbm.25783
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating distinct and converging neural correlates of types of systemic environmental exposures

Abstract: Systemic environmental disadvantage relates to a host of health and functional outcomes. Specific structural factors have seldom been linked to neural structure, however, clouding understanding of putative mechanisms. Examining relations during childhood/preadolescence, a dynamic period of neurodevelopment, could aid bridge this gap. A total of 10,213 youth were recruited from the Adolescent Brain and Cognitive Development study. Self-report and objective measures (Census and Federal bureau of investigation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 99 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Several studies have demonstrated the effect of neighbourhood disadvantage on brain structure in youth and adults, such as widespread lower volume of WM and GM (178,179), including hippocampus (168,(179)(180)(181), amygdala (168), dlPFC and dorsomedial PFC, superior frontal gyrus (181), IFG and ACC (182). In addition, smaller surface area and cortical thinning was observed in the frontal, parietal, and temporal lobes, cingulate and insula (183)(184)(185)(186)(187). Finally, neighbourhood disadvantage was linked to atypical neurodevelopmental trajectories during adolescence, indicating delayed brain development (188,189).…”
Section: Regional Socioeconomic Statusmentioning
confidence: 99%
“…Several studies have demonstrated the effect of neighbourhood disadvantage on brain structure in youth and adults, such as widespread lower volume of WM and GM (178,179), including hippocampus (168,(179)(180)(181), amygdala (168), dlPFC and dorsomedial PFC, superior frontal gyrus (181), IFG and ACC (182). In addition, smaller surface area and cortical thinning was observed in the frontal, parietal, and temporal lobes, cingulate and insula (183)(184)(185)(186)(187). Finally, neighbourhood disadvantage was linked to atypical neurodevelopmental trajectories during adolescence, indicating delayed brain development (188,189).…”
Section: Regional Socioeconomic Statusmentioning
confidence: 99%